2008
DOI: 10.1007/s00464-008-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open liver segmentectomy: prospective, case-matched, intention-to-treat analysis of clinical outcomes and cost effectiveness

Abstract: Laparoscopic liver segmentectomy and bisegmentectomy are feasible, safe and cost effective compared to similar open resections. Large-scale application of laparoscopic liver surgery could translate into significant savings to hospitals and health care programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
101
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(117 citation statements)
references
References 35 publications
13
101
0
3
Order By: Relevance
“…Although liver resection specific complications were reported in similar rate with open surgery, rate of liver decompensation among cirrhotic patients has a trend to decrease at application of laparoscopic approach (63,71,76). General morbidity -cardiopulmonary complications, abscesses and wound complications have a tendency to reduce in application of laparoscopic approach (59,63,64,68,71,77). Rate of incisional hernias after LHR is appreciably lower then after the open counterpart (24,72).…”
Section: Mortality Postoperative Morbiditymentioning
confidence: 98%
“…Although liver resection specific complications were reported in similar rate with open surgery, rate of liver decompensation among cirrhotic patients has a trend to decrease at application of laparoscopic approach (63,71,76). General morbidity -cardiopulmonary complications, abscesses and wound complications have a tendency to reduce in application of laparoscopic approach (59,63,64,68,71,77). Rate of incisional hernias after LHR is appreciably lower then after the open counterpart (24,72).…”
Section: Mortality Postoperative Morbiditymentioning
confidence: 98%
“…However, less severe complications such as postoperative ascites, wound infection, and pneumonia remain common. Recently, laparoscopic liver resection has become popular, especially for minor resections or resection of the left lateral segment, and may reduce morbidity of liver resection [256]. However, thus far, no randomized trial comparing open and laparoscopic liver resection has been reported.…”
Section: Liver Resectionmentioning
confidence: 99%
“…We were not able to identify appropriate HRGs in the NHS reference costs for laparoscopic liver resection, but we identified a cost study reported by Polignano et al 173 in which the costs of elective laparoscopic and open liver segmentectomy, performed with an intention to treat the disease, were compared (Table 114) The two groups were homogeneous by age, sex, coexistent morbidity and magnitude of resection. Hospital costs were obtained from the Scottish Health Service Costs (ISD Scotland) and average costs were calculated.…”
Section: Independent Economic Assessmentmentioning
confidence: 99%